Gambaran Umum Pendidikan Sekolah Berkebutuhan Khusus di Kabupaten Ketapang Provinsi Kalimantan Barat - Adi Sugiarto; Usman Radiana; Nurwahid Nurwahid; Megawati Megawati (Publikasi Indonesia, 2022)
This research is an attempt to find out more about the implementation of education management in Special Schools in Ketapang district, West Kalimantan Province. The research method chosen is descriptive qualitative and also with a literature review in the data collection process. The special school which is the subject of research is led by a principal who is in charge of being the leader and manager of the school. Extraordinary Schools are schools that run inclusive or special education, in this school the condition of students has different characteristics, the location of the school is in the middle of the city, and students with different conditions of impairment make the management of education in schools with special needs not run optimally. Therefore, it is necessary to know more about how schools deal with these problems.